Менеджмент економічної галузі за умов нагальної потреби оновлення кадрового потенціалу - BURIAK, YEVHEN; VEREZOMSKA, IRYNA; YAREMCHUK, SERHII (My University, 2023)
The economic sector is constantly evolving, and in order to remain competitive, companies must regularly update their workforce to keep pace with new technologies and market demands. This paper examines the challenges and opportunities associated with managing human resources in the economic sector, particularly under conditions of urgent need for updating personnel potential. The purpose of the paper is to analyze the current state of human resource management in the economic sector and to propose strategies for updating personnel potential in response to changing market demands and technological advancements. The paper examines the role of leadership, training and development, and other key factors in promoting innovation and growth in the economic sector. Results. The paper finds that effective human resource management is critical for companies operating in the economic sector. The study identifies a number of key challenges, including difficulties in attracting and retaining top talent, gaps in employee skills and knowledge, and the need for ongoing training and development programs. The paper also highlights the potential benefits of investing in workforce development, including increased productivity, improved employee morale and job satisfaction, and a more competitive position in the marketplace. Conclusion. In conclusion, effective human resource management is essential for companies operating in the economic sector, particularly in the face of rapidly changing market demands and technological advancements. By investing in training and development programs, updating recruitment strategies, and promoting a culture of innovation and growth, companies can position themselves for long-term success in a dynamic and competitive business environment.
Management of the economic sector under the conditions of the urgent need to update personnel potential
Keywords: менеджмент; економічна галузь; кадровий потенціал; оновлення